THE RELATIONSHIP OF COMMUNICATION BETWEEN ADOLESCENTS AND PARENTS AND PEER GROUP WITH PREMARITAL SEXUAL BEHAVIOR OF ADOLESCENT - Rahmadini Faricha Hakim; Firdawati Firdawati; Lisma Evareny (SEAJOM: The Southeast Asia Journal of Midwifery, 2022)
Developments the current era of globalization makes people's lifestyles more free. This can be seen from premarital sex behavior among teenagers. Premarital sex behavior can cause depression, unwanted pregnancy and transmission of sexually transmitted diseases. Many factors influence mainly from the family environment and community environment. The purpose of this study was to determine the relationship of communication between adolescents and parents and peer group with premarital sexual behavior of adolescents. This study uses analytical survey methods with Cross Sectional design. The sample in this study were adolescents who met the inclusion and exclusion criteria totaling 87 people. The sampling technique used is simple random sampling. Data were analyzed by univariate to describe the frequency distribution of each of the variables studied and bivariate by using the chi-square test. The results showed that there was a relationship between adolescent communication with parents (p= 0.01) with premarital sex behavior and there was no statistical test on the variable peer group because in the peer group weakthere was a proportion of 0% teenagers who were at low risk. There is a significant relationship between adolescent communication with parents and premarital sex behavior in adolescents. For this reason parents can provide communication that educates teenagers on topics related to sexuality and openness to communication so parents can control and provide good direction to their children.